Primary health care in Nigeria: best practices and quality of care in Nigeria - Phyllis O Ogah; Nkolika Uguru; Chinyere Okeke; Nurudeen Mohammed; Oritseweyimi Ogbe; Wende G Ashiver; Muyiwa Aina (BMC, 2024)
Abstract Introduction The significance of Primary Healthcare Centers (PHCCs) in fostering health equity and enhancing health outcomes cannot be overstated, especially in low and middle-income countries. This paper's primary area of interest is to create evidence and innovation for PHCs, with a particular emphasis on underserved groups. Thus, the study aimed to investigate the state of primary health care in Nigeria, with a particular emphasis on best practices, challenges to best practices, and quality of care. Methodology A cross-sectional quantitative study was conducted to collect secondary data from 29 primary healthcare facilities. The data was collected using staff and facility activity indicators over a year (2022). Descriptive statistics and chi-square tests were used to analyze the collected data. Result Our study data showed that all of the PHCCs have service rosters that can be utilized for follow-up with patients. About 85 (84.1%) respondents have reported that deliveries were taken by the reporting midwife, and 55 (54.5%) respondents indicated that their facilities provided on-the-job training to their staff. This is considered as the best practice in the facility. However, the majority of the PHCCs (71.3%) lacked assessment teams, which was found to have a negative impact on the quality of healthcare provided at these facilities (p < 0.05). Conclusion Our study underscores the pressing need for primary healthcare services in Nigeria. Government authorities and healthcare providers must take action to overcome the challenges of limited capacity, service delivery, and quality of care. By adopting effective strategies and ensuring access to primary healthcare, citizens' health outcomes can be greatly enhanced. Thus, it is essential to revamp and optimize healthcare facilities to establish an efficient healthcare system that caters to the needs of all citizens.